2014
DOI: 10.1097/qad.0000000000000478
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of HIV reservoir characteristics with immune status and viral rebound kinetics in an HIV therapeutic vaccine study

Abstract: Objectives To evaluate the impact of therapeutic HIV vaccination on the HIV reservoir, and assess the relationship of the viral reservoir with HIV-specific immune status and viral rebound kinetics. Design Retrospective analysis of ACTG A5197, a randomized, placebo-controlled trial of a therapeutic rAd5 HIV-1 gag vaccine. Methods Participants received vaccine/placebo at weeks 0, 4, and 26 prior to a 16-week analytic treatment interruption (ATI) at week 38. Cell-associated HIV-1 RNA and DNA (CA-RNA and CA-DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“…In any case, we observed changes in the correlations between viral reservoir measurements and HIV-1-specific T cell immune responses before and after vaccinations in both DC-HIV-1 and DC-control groups. No correlations were observed before vaccination, in accordance with the data of other authors who have not found significant associations between the viral reservoir and HIV-specific CD8 T cell counts (19,25). Conversely, a significant inverse correlation was observed after vaccination (and before cART interruption) in vaccinated patients, and a direct correlation was observed in controls.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In any case, we observed changes in the correlations between viral reservoir measurements and HIV-1-specific T cell immune responses before and after vaccinations in both DC-HIV-1 and DC-control groups. No correlations were observed before vaccination, in accordance with the data of other authors who have not found significant associations between the viral reservoir and HIV-specific CD8 T cell counts (19,25). Conversely, a significant inverse correlation was observed after vaccination (and before cART interruption) in vaccinated patients, and a direct correlation was observed in controls.…”
Section: Discussionsupporting
confidence: 81%
“…A recent therapeutic vaccine clinical trial using an autologous dendritic cell-based therapeutic HIV vaccine (similar to our approach) demonstrated an increase of residual viremia and cell-associated RNA after vaccination despite continuous ART (23). Another 2 studies did not find any effect of immunizations on the viral reservoir, despite the fact that both demonstrated an increase in HIV-specific T cell responses (19,24). Finally, Persaud et al (20) found that HIV recombinant poxvirus-based vaccinations administered to in- fected young adults who were receiving durable effective cART resulted in a modest but measurable and statistically significant transient decrease in the frequencies of latently infected CD4 ϩ T cells detected by 40 weeks following the first vaccine dose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations